2022
DOI: 10.3389/fnhum.2022.760360
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between White Matter Hyperintensity Burden and Regional Brain Volumetry in Patients With Alzheimer's Disease

Abstract: BackgroundWhite matter hyperintensities (WMHs) and regional brain lobe atrophy coexist in the brain of patients with Alzheimer's disease (AD), but the association between them in patients with AD still lacks comprehensive investigation and solid imaging data support.ObjectiveWe explored whether WMHs can promote the pathological process of AD by aggravating atrophy in specific brain regions and tried to explain the regional specificity of these relationships.MethodsA sample of 240 adults including 180 normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The findings presented identify cerebrovascular pathology as a candidate mechanism driving MTL degeneration associated with OSA-related hypoxemia. Prior studies also support this possibility, suggesting a strong link between WMH burden and MTL atrophy 143146 which the present findings extend by implicating hypoxic burden during REM sleep as a contributor to this link. AD patients with periventricular WMH had a significantly increased risk of progression of MTL atrophy compared to those without baseline periventricular WMH 144 .…”
Section: Discussionsupporting
confidence: 84%
“…The findings presented identify cerebrovascular pathology as a candidate mechanism driving MTL degeneration associated with OSA-related hypoxemia. Prior studies also support this possibility, suggesting a strong link between WMH burden and MTL atrophy 143146 which the present findings extend by implicating hypoxic burden during REM sleep as a contributor to this link. AD patients with periventricular WMH had a significantly increased risk of progression of MTL atrophy compared to those without baseline periventricular WMH 144 .…”
Section: Discussionsupporting
confidence: 84%
“…The whole scale considers DWMHs to a greater extent, whereas the first two grades of PWMHs are almost considered normal in the whole WM form of the Fazekas scale. Research has found that DWMHs have greater and more correlative diagnostic value to clinical presentation value (see: White matter hyperintensities); however, specific guidelines on which scale to use have not yet been established, and in both scales, there is a possibility to underdiagnose or overdiagnose patients [ 59 ].…”
Section: Standardized Assessmentmentioning
confidence: 99%
“…The prevalence of WMH is 10–20% for people in their 60 s, reaching 100% in people over the age of 90 (Smith et al, 2017 ). In the aging population, WMHs can contribute to a higher rate of brain atrophy in beyond-normal brain aging, particularly in regions related to AD (Habes et al, 2016 ), such as the medial temporal lobe, insular lobe, and temporal lobe (Cao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%